The Effect of the 7P Marketing Mix and Service Quality on Customer Satisfaction - Duwi Putri Pramesty; S. Sapar; Muhammad Aqsa (Yayasan Ahmar Cendekia Indonesia, 2022)
This study aims to describe and analyze the marketing mix and service quality on customer satisfaction at BRI Palopo Branch. The research sample was taken using the Simple Random Sampling Technique. Data analysis used variant-based structural equation modeling (VB SEM) with the help of Smart PLS software version 3.3. The results of this study indicate that the marketing mix has a significant effect on customer satisfaction of 0.619 units with a t count value: 8,400> t table 1,666 with a P-value of 0.000 <0.05. Service quality has no significant effect on customer satisfaction of 0.103 units with a t-value: 0.632 <t table 1.666 with a P-value of 0.527>0.05. The joint influence of the marketing mix (X1) and service quality (X2) on customer satisfaction (Y) is 40.6 percent, while 59.4 percent is influenced by other variables not observed in this study.